Information for patients with cancer. Does personalization make a difference? Pilot study results and randomised trial in progress. - Jones, R. (American Medical Informatics Association, 1996)
Although there are a number of groups working on the provision of personalized patient information there has been little evaluation. We have developed and piloted a method of giving patients on-line access to their own medical records with associated explanations. We are comparing, in a randomised trial, personalized with general computer based information for patients undergoing radiotherapy for cancer. We present results from the pilot study and the evaluation methods to be employed.